THE IMPLEMENTATION OF SUGGESTOPEDIA IN DIFFERENT LANGUAGE CONTEXTS (American Journal of Pedagogical and Educational Research, 2023)
This paper is a qualitative study and aims to explain the nature of the method of Suggestopedia as a whole together with defining core principles of this method. It further discusses the overall findings of previous studies on effectiveness of Suggestopedia in different language contexts that has attempted to improve a particular language aspect with the help of this method.